Mortality of People With Alzheimer's Disease and Psychiatric Morbidity: A Nationwide Finnish Cohort Study - Alastalo, Aleksi; Haapea, Marianne; Nordström, Tanja; Tolppanen, Anna‐Maija; Miettunen, Jouko; Nietola, Miika; Hartikainen, Sirpa; Jääskeläinen, Erika (Wiley, 2026)
Objectives
Psychiatric comorbidities are common in Alzheimer's disease (AD), and they have a negative impact on quality of life, but their impact on mortality remains unclear. This study examined mortality among persons with AD and psychiatric morbidity compared to persons with AD without psychiatric morbidity. This is the first study to analyze Alzheimer's disease mortality based on the timing of earlier psychiatric morbidity.
Methods
We utilized the nationwide register-based MEDALZ cohort, including 70,718 Finnish individuals diagnosed with AD between 2005 and 2011. Individuals were categorized into four groups based on the occurrence of their hospital-treated psychiatric diagnosis before the diagnosis of AD. Mortality was assessed over an 8-year follow-up. Chi-square test was used to compare the differences between the four groups in terms of causes of death and annual cumulative mortality. We determined cumulative mortality curves and hazard ratios, stratified by age, gender, cardiovascular disease, and the year of AD diagnosis.
Results
During the 8-year follow-up, 70.4% of the AD cohort had died. Persons with earlier psychiatric morbidity had an AD diagnosis 1.4–4.3 years earlier and died 1.4–4.1 years younger. Mortality risk was slightly higher among those with psychiatric morbidity compared to those without (adjusted HRs 1.03–1.41), with the effect decreasing over the years of follow-up. Mortality risk was not affected by the timing of psychiatric morbidity.
Conclusion
Psychiatric comorbidity is associated with earlier AD onset and reduced lifespan; however, post-diagnosis survival appears to be largely determined by AD progression itself.